Ocular hemodynamics in patients with stage I-IV keratoconus (Ukrainian Journal of Ophthalmology, 2026)
Background.  Keratoconus is a progressive dystrophic condition of the cornea. Dystrophic changes in keratoconus are observed in the connective tissues of the sclera, drainage area, and iris. The role of a vascular factor in the development of such diseases as glaucoma, uveitis, and cataract is well-known. In this respect, studying the ocular blood supply in keratoconus appears to be reasonable.Material and Methods. Rheography was performed in 90 patients (125 eyes), aged 16-39, with keratoconus of stages I-V  and the volume pulse blood flow in the eye was determined according to rheographic coefficient (RQ (‰)). In 21 eyes, stage IV-V keratoconus was accompanied by ocular hypertension and non-penetrating deep sclerotomy was performed. Depending on volume pulse blood flow rates and a vascular tone in the eye, 14 patients (28 eyes) with stage I-V keratoconus were treated using anti-ischemic and antioxidant drugs. Results. The decreased blood flow rates were noted in the eyes in each group as compared to norm. Volume blood flow was decreased by 26.7% in the eyes of the patients with stage II, III, and IV and  by 44.8% in stage V keratoconus  as compared to healthy patients of the same age. Volume blood flow RQ was 2.36±0.40 ‰ in stage IV-V keratoconus, complicated by ocular hypertension above 27 mmHg, i.e. by 43.8% lower than the age norm. Volume blood flow in the patients with stage IV keratoconus and intraocular hypertension was by 22.3% lower as compared with the uncomplicated course of stage IV keratoconus. Non-penetrating deep sclerotomy (NPDS) for ocular hypertension in the patients with stage IV-V keratoconus facilitated an increase in volume blood flow by 72.5%; RQ increased from 2.36±0.4 ‰ to 4.07±0.7 ‰), р
Keywords: keratoconus; ocular hemodynamics; rheography